Comparison of tensiometer. Thermal conductivity and capacitance sensor measurements of pore water pressure in compacted clay columns - Indrawan, I.G.B; Williams, D.J.; Scheuermann, A. (CRC Press, 2014)
Real-time pore water pressure measurements have been made automatically and continuously with tensiometer (GT), thermal conductivity (TC) and capacitance (MP) sensors in laboratory compacted clay columns. Although GT, TC and MP sensors have been commonly used in many applications, there has rarely been any attempt to compare the measurements made by the different sensors or to evaluate their long-term performance, especially for application in compacted clay in a high salinity environment and under a high hydraulic gradient. In this study, GT, TC and MP sensors were calibrated and subsequently installed at various elevations in 303 mm diameter by 300 mm high compacted clay columns subjected to wetting by a 100 kPa saline water pressure, followed by subsequent drying. The calibration and measurement results showed that the GT sensors allowed measurements not only of negative pore water pressure, but also of positive pore water pressure. While the GT sensors allowed the measurement of pore water pressure down to -80 kPa, the TC and MP sensors were able to measure much higher negative pore water pressures. The TC and MP sensors were, however, found to have large sensor-to-sensor variations, hysteretic behaviour upon drying and wetting, and slow equilibration times. Unlike the GT and TC sensors, the long-term performance of the MP sensors was found to be affected by the salinity of the compacted clay.